Underway CTD data collected during Maria S. Merian cruise MSM89 - Johannes Karstensen; Gerd Krahmann (PANGAEA, 2023)
The UCTD is a CTD system that can be deployed from a moving ship, allowing for the sampling of water masses at high horizontal resolution (ranging from less than 1 km for the Rapidcast system to 10 km for deep UCTD casts) with good accuracy of the pressure, temperature, and conductivity sensors. Processing of the data involved mostly the fall-rate dependent correction of the thermal lag of the conductivity sensor and followed the approach described by Ullman and David (2014). Subsequently the corrected data was calibrated against the calibrated coincident Thermosalinograph and the calibrated nearby CTD data. The typical accuracies of the final pressure, temperature, and salinity data are 1 dbar, 0.01 °C, and 0.01 g/kg, respectively.